2020
DOI: 10.12974/2312-5411.2020.07.1
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Parameters of Pregnant Kano Brown Does Vaccinated Against Peste Des Petits Ruminants in Nigeria

Abstract: Peste des petits ruminants (PPR) is an endemic disease of small ruminants globally and, the disease controlled primarily by vaccination. The aim of this study was to determine the changes in haematological parameters of pregnant goats vaccinated against PPR. Ten pregnant female goats were obtained for the purpose of this study. The pregnant goats were at about the same stage of pregnancy, confirmed by ultrasonography. Vaccination using the Nigeria 75/1 PPR virus vaccine was done at first trimester of pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Some cases found that infection of some microorganism or viruses may can decrease lymphocyte counts below a normal range (lymphophenia). 21 The research by 22 about the effect fraction of lemongrass (C. nardus) against viral activity with the three treatment methods were designed to indicate whether the antiviral actions of fractions occurs before, during or after viral entry into the cells. The result is at 0.1 LC50, the C. nardus fractions were more effective when cells treated with the fractions before being inoculated with the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases found that infection of some microorganism or viruses may can decrease lymphocyte counts below a normal range (lymphophenia). 21 The research by 22 about the effect fraction of lemongrass (C. nardus) against viral activity with the three treatment methods were designed to indicate whether the antiviral actions of fractions occurs before, during or after viral entry into the cells. The result is at 0.1 LC50, the C. nardus fractions were more effective when cells treated with the fractions before being inoculated with the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Some types of molecular data found in the reviewed articles do not fit the description of omics data. These non-omics data are mainly: (a) data derived from IHC techniques [35]; and (b) genetic data obtained with PCR techniques [36].…”
Section: Molecular Datamentioning
confidence: 99%